Financial Performance and Labour Involvement of Small-Scale Dairy Farmers: A Case Study at the SAE Pujon Dairy Cooperative - Febrianto, Nanang; Susilawati, Trinil; Hartono, Budi; Akhiroh, Puji; Puspita Anugra Yekti , Aulia; Prafitri, Rizki; Helmi, Muhammad; Masyithoh, Dewi; Nasir Shamsudin , Mad (Jurnal Ilmu-Ilmu Peternakan, 2023)
In Indonesia, small-scale dairy cattle farming dominates, constituting 80% of the industry, with economic pursuits secondary to subsistence needs. Challenges include limited green fodder, declining farmers, low milk quality, diseases, and inadequate infrastructure. Despite these issues, dairy farming persists, particularly in East Java's Malang Regency, a major contributor to national dairy cattle population and milk production. The significance of Pujon Sub-District comes to the forefront, housing the Sinau Andandani Ekonomi (SAE) Pujon Cooperative established in 1975. This cooperative plays a pivotal role in supporting small-scale farmers in Pujon, actively addressing challenges through collaborative efforts. This cooperative facilitates small-scale farmers in Pujon, addressing challenges through collective efforts. In such systems, family labor, including women and children, is integral due to limited availability. The study aims to analyse the income of dairy cattle farmers and their labour allocation as the members of SAE Pujon Cooperative, Pujon District, Regency of Malang. The data of the farm management parameters were collected through a survey at the study area. The results indicate that the average income of the farmers is IDR 4,306,798 per month. Regarding labour allocations, wives work to household affairs and husbands focus more on farming activities. The research concludes that the income of dairy farmers and their labour allocation are related to the farm scale.